Spatial Identities at the Russo-Chinese Border: The Cases of Blagoveshensk and Heihe - M. I. Tislenko (Сравнительная политика)
In this article the phenomenon of Blagoveshchensk and Heihe – border ‘twin cities’ – is in the spotlight of the researcher. The author observes, how these cities separated from each other by the Amur and the state border have been able to construct their own model of spatial identity taking into account Russian and Chinese national identities.